Answers

2014-07-18T14:16:11+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

1) rearrange the equation such that it is in the form ax² + bx = c
2) the value of a should be 1. If a≠1, divide the whole equation by a.
3) determine the value of  b in  x² + bx = c.  Find (b/2)².
4) add  (b/2)
²  to both sides of the equation
5) simplify and solve for x


Step by step example:

(1)     2x
² + 12x = 2

(2)       x² + 6x = 1

(3)   b=6   ;    (b/2)² = 9
         
(4)    x² + 6x + 9  =  1 + 9

(5)        (x+3)² = 10      ...then solve for x.
0